Suppressing Twin Formation in Bi2Se3 Thin Films. Issue 5 (2nd May 2014) - Tarakina, N. V.; Schreyeck, S.; Luysberg, M.; Grauer, S.; Schumacher, C.; Karczewski, G.; Brunner, K.; Gould, C.; Buhmann, H.; Dunin‐Borkowski, R. E.; Molenkamp, L. W.
<x xml:space="preserve">Abstract</x> The microstructure of Bi2Se3 topological‐insulator thin films grown by molecular beam epitaxy on InP(111)A and InP(111)B substrates that have different surface roughnesses has been studied in detail using X‐ray diffraction, X‐ray reflectivity, atomic force microscopy and probe‐corrected scanning transmission electron microscopy. The use of a rough Fe‐doped InP(111)B substrate results in complete suppression of twin formation in the Bi2Se3 thin films and a perfect interface between the films and their substrates. The only type of structural defect that persists in the twin‐free films is an antiphase domain boundary, which is associated with variations in substrate height. We also show that the substrate surface termination influences which family of twin domains dominates.